Dispersive Liquid‐Liquid Microextraction (DLLME) Based on Solidification of Switchable Hydrophilicity Solvent Coupled with High‐Performance Liquid Chromatography (HPLC) with Photodiode Array (PDA) Detection for the Determination of Pyrethroid Pesticides in Grains. (3rd July 2023) - Cao, Hui; Chen, Zixin; Kong, Yanan; Wei, Ziqi; Ye, Tai; Yuan, Min; Yu, Jinsong; Wu, Xiuxiu; Hao, Liling; Yin, Fengqin; Xu, Fei
Abstract: Rapid dispersive liquid-liquid microextraction (DLLME) based on the solidification of a switchable hydrophilicity solvent (SHS) was established for the preconcentration of pyrethroid pesticides from grain prior to determination using high‐performance liquid chromatography (HPLC) with photodiode array (PDA). Lauric acid was selected to be the switchable hydrophilicity solvent due to its conversion between hydrophobic and hydrophilic forms and solidification at low temperature, thereby avoiding a time-consuming centrifugation step. The results show that the optimal conditions for pyrethroid pesticides included 30 mmol/L lauric acid, hydrochloric acid as the hydrogen donor, a 1:1.8 stoichiometric ratio of sodium laurate and hydrochloric acid, an extraction temperature of 50 °C, an extraction time of 8 min, and a solidification time of 3 min. Under the optimal conditions, this approach provided a high enrichment factor (308.4 to 330.2), a short pretreatment period of less than 15 min, and sensitive detection limits from 5 to 20 ng/g suitable for the analysis of food. The method was employed for the determination of pyrethroid pesticides in grain. The recoveries were 84.3% to 115.7%, and the relative standard deviation was less than 9.9%.